Resilience of Madurese Generation Z Migrants in Contemporary Turkey:The Internalization of the “Asapok Angin and Abhental Ombhe” Philosophies and Religiosity in Addressing Socio-Cultural Adaptation Challenges - Aulya Nadlira Alfasya; Listyo Yuwanto (Jurnal Ragam Pengabdian, 2026)
Generation Z has emerged as a digitally native cohort facing increasingly complex psychological and socio-cultural challenges, particularly in the context of contemporary international migration. This study aims to examine how Madurese Generation Z migrants in Turkey construct psychological resilience through the internalization of local cultural philosophies—Asapok Angin and Abhental Ombhe—and religiosity. Guided by an interpretive paradigm, this research employed a phenomenological approach to capture lived experiences of two Madurese Generation Z migrants who concurrently functioned as international students and part-time workers in Turkey. Data were collected through in-depth semi-structured interviews and analyzed using systematic thematic analysis involving data condensation, categorization, and theme development. The findings demonstrate that resilience is constructed through three interrelated strategies: strong commitment to personal goals, spirituality-based religious coping, and social support within the Madurese migrant community. The philosophies of Asapok Angin and Abhental Ombhe operate as internalized moral frameworks that reinforce perseverance, emotional regulation, and meaning-making in response to academic, economic, linguistic, and psychological pressures. This study concludes that local cultural values and religiosity function as critical psychological resources that strengthen the resilience of young migrants, underscoring the importance of culturally grounded approaches in understanding youth resilience within a globalized migration context.